2021
DOI: 10.1080/1828051x.2021.1961616
|View full text |Cite
|
Sign up to set email alerts
|

Maternal cholecalciferol supplementation during gestation improves antioxidant capacities in gilts and piglets

Abstract: Various studies have evaluated the relationship between cholecalciferol (vitamin D 3 ) and reproductive performance. This study aimed at investigating the effects of maternal D 3 supplementation during gestation on reproductive performance and antioxidant capacities of gilts and their offsprings. Twenty-three Landrace  Yorkshire gilts were randomly allocated into two groups and fed on one of the following two diets during gestation: control diet or D 3 supplemented diet. It was found that D 3 supplementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Our previous study has shown that the serum concentration of 25-OHD 3 in newborn piglets was significantly increased by maternal VD 3 supplementation. 11 Here we showed that the serum concentrations of 25-OHD 3 in the weaning piglets were…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Our previous study has shown that the serum concentration of 25-OHD 3 in newborn piglets was significantly increased by maternal VD 3 supplementation. 11 Here we showed that the serum concentrations of 25-OHD 3 in the weaning piglets were…”
Section: Discussionmentioning
confidence: 84%
“…Our previous report has shown that sows supplemented with VD 3 during gestation tended to have more total born and born alive piglets, without changes in the birth weight per piglet or the farrowing duration of sows. 11 Besides, VD 3 supplementation during gestation also increased the placenta weight of sows. 11 The present study showed that the litter size, litter weight and ADG of piglets were not changed by maternal VD 3 supplementation.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations